Cressleaf Groundsel (Butterweed) Identification and Management in Pastures - Brent A. Sellers; Jay Ferrell (EDIS)
Butterweed is a winter annual that is toxic to both cattle and horses. This 2-page fact sheet provides an overview of the plant as well as herbicide recommendations. Written by Brent Sellers and Jay Ferrell, and published by the UF Agronomy Department, May 2016.